2005
DOI: 10.1385/bter:105:1-3:205
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Concentrations During Mice Gestation

Abstract: Severe maternal zinc deficiency has a devastating effect on pregnancy outcome. Studies of humans and experimental animals show that maternal zinc deficiency can cause infertility, prolonged labor, intrauterine growth retardation, teratogenesis, severe immunological deficiencies, or fetal death. The additional need for zinc during pregnancy can be met by an increase in zinc intake. An increase in zinc supplements, when excessive, can cause a decrease in copper. Therefore, it is important to determine the zinc a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Copper can inhibit the secretion from cervical glands and endometrial cells, and affect the reproductive process; also, increased copper levels can interfere with zinc and manganese functions [24,25]. A relationship between copper, zinc and unexplained infertility has been reported [26], but there is still debate about the relationship between iron and unexplained infertility. Fu et al [27] found that there was no significant change in serum iron levels in infertile patients.…”
Section: Discussionmentioning
confidence: 99%
“…Copper can inhibit the secretion from cervical glands and endometrial cells, and affect the reproductive process; also, increased copper levels can interfere with zinc and manganese functions [24,25]. A relationship between copper, zinc and unexplained infertility has been reported [26], but there is still debate about the relationship between iron and unexplained infertility. Fu et al [27] found that there was no significant change in serum iron levels in infertile patients.…”
Section: Discussionmentioning
confidence: 99%